1998
DOI: 10.1111/j.1572-0241.1998.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

Milk Thistle ( Silybum marianum ) for the Therapy of Liver Disease

Abstract: Silymarin, derived from the milk thistle plant, Silybum marianum, has been used for centuries as a natural remedy for diseases of the liver and biliary tract. As interest in alternative therapy has emerged in the United States, gastroenterologists have encountered increasing numbers of patients taking silymarin with little understanding of its purported properties. Silymarin and its active constituent, silybin, have been reported to work as antioxidants scavenging free radicals and inhibiting lipid peroxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
211
0
8

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 644 publications
(233 citation statements)
references
References 15 publications
2
211
0
8
Order By: Relevance
“…Among various plants, Silybum marianum (milk thistle) is the most researched plant for the treatment of liver diseases from ancient times until now (9,10). Several studies showed that the extract of this plant protects the liver against chemical and environmental toxins (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Among various plants, Silybum marianum (milk thistle) is the most researched plant for the treatment of liver diseases from ancient times until now (9,10). Several studies showed that the extract of this plant protects the liver against chemical and environmental toxins (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin and its active constituent, silybin, are believed to act as antioxidants, scavenging free radicals and inhibiting lipid peroxidation, thus finding use in chronic liver disorders [87,88]. It is believed to be safe and well-tolerated, with very minor side effects reported when taken within the recommended dose range (gastrointestinal upset, mild laxative effect and rare allergic reaction).…”
Section: Liver Diseasesmentioning
confidence: 99%
“…Silymarin, an antioxidant flavonoid complex derived from the herb milk thistle (Silybum marianum) has long been used in the treatment of liver diseases [12,21,27,33]. This property seems to be due to its ability to scavenge free radicals and to chelate metal ions [6,8].…”
Section: Introductionmentioning
confidence: 99%